Low-carbon composite cementing material and preparation method thereof

By compounding compound cementitious materials of mineralization and regenerating micro powder, granulated blast furnace slag, fly ash and kiln ash, the problem of difficult cement replacement in the existing technology is solved, efficient cement replacement and carbon dioxide fixation are achieved, and the improvement of The compressive strength and environmental protection of the material.

CN119320246APending Publication Date: 2025-01-17SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411446435.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing technology is difficult to achieve a high proportion of cement in cementitious materials under low energy consumption, which makes it difficult to achieve the carbon reduction goal of the construction industry, and the absorption of industrial solid waste in the construction industry is restricted. The existing composite cementitious materials are The solid waste is low and the compressive strength is insufficient.

Method used

Using composite cementitious materials with compounded mineralized regenerated powder, granulated blast furnace slag, fly ash and kiln ash, the granulated blast furnace slag powder and mineralized regenerated powder are obtained through mechanical treatment and mineralization treatment, and mixed evenly to prepare low-carbon Composite cementitious materials make full use of waste concrete and industrial solid waste to achieve high proportional replacement of cement.

Benefits of technology

It has achieved a high proportion of cement substitution (40-80%), reduced carbon dioxide emissions, improved the compressive strength and environmental protection of the material, low cost, strong applicability, and can effectively fix and store carbon dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320246A_ABST
    Figure CN119320246A_ABST
Patent Text Reader

Abstract

The invention discloses a low-carbon composite cementing material and a preparation method thereof, and belongs to the field of solid waste resource utilization and green building materials. The composite cementing material comprises the following components in percentage by mass: 20%-60% of cement clinker, 15%-35% of mineralized regenerated micro powder, 15%-45% of granulated blast furnace slag, 2.5%-10% of fly ash and 2.5%-5% of kiln dust, wherein the mineralized regenerated micro powder is obtained from regenerated micro powder of waste concrete. The preparation method of the low-carbon composite cementing material comprises the following steps: uniformly mixing mineralized regenerated micro powder subjected to mechanical treatment and CO2 mineralization treatment with granulated blast furnace slag, cement clinker, fly ash and kiln dust to obtain the composite cementing material. The low-carbon composite cementing material provided by the invention not only can effectively reduce the consumption of cement clinker and greatly reduce the CO2 emission of the cement industry, but also provides an effective technical scheme for resource utilization of solid wastes such as waste concrete and granulated blast-furnace slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid waste resource utilization and green building materials, and specifically relates to a low-carbon composite cementitious material and a preparation method thereof. Background Art

[0002] The demolition and reconstruction of buildings will not only generate a large amount of waste concrete, which will occupy a large amount of land during the stacking or landfill process, but also increase the demand for cementitious materials such as cement, resulting in a large amount of CO 2 According to statistics, in 2023 alone, the CO emissions from cement production will 2 The emission reached 1.25 billion tons, the output of waste concrete was as high as 2.5 billion tons, but the recycling rate was less than 20%. Therefore, improving the recycling rate of waste concrete resources and developing composite cementitious materials to replace cement have become urgent issues to be solved in the development of the industry.

[0003] At present, the common method in the cement industry is to add solid wastes such as fly ash and steel slag powder into cement to form composite cementitious materials, which have been applied in many construction scenarios. At the same time, in recent years, the recycled micropowder obtained by crushing waste concrete can be used as cement admixture, which can reduce the use of cement in the construction industry while realizing the recycling of waste concrete. However, it is worth noting that the solid waste content in these composite cementitious materials is low, and it is difficult to exceed 30% under the premise of ensuring the performance of cementitious materials. When the solid waste content is high, the performance of cementitious materials will be significantly reduced, especially the compressive strength. There are also studies that can directly prepare cement or cementitious materials with similar properties from waste concrete or solid waste by heat treatment, but this often requires high energy consumption to achieve. In general, although a lot of research has been carried out on the replacement of cement materials, no relevant solutions have been proposed to achieve a high proportion of cement in cementitious materials at low energy consumption, which brings difficulties to the realization of carbon reduction goals in the field of building materials.

[0004] With the increasing requirements of actual application scenarios, the current method of directly mixing industrial solid waste with cement to prepare composite cementitious materials is limited, which limits the disposal of industrial solid waste in the construction industry. At the same time, most of the current research on recycled micropowder systems is concentrated in the laboratory stage. Commonly used methods such as heat treatment and alkali excitation will increase the energy consumption cost of recycling waste concrete, which is not conducive to the large-scale promotion of technology in the construction, coal-fired power, steel and other industries. Therefore, in order to achieve the goals of resource utilization of waste concrete and industrial solid waste and replacement of cement materials, it is currently a problem that needs to be solved to develop a composite cementitious material that can achieve high performance at a lower cost. Summary of the invention

[0005] The present invention overcomes the shortcomings of the prior art and proposes a low-carbon composite cementitious material and preparation method, which has the characteristics of low cost, strong environmental friendliness and resource recycling. The method can not only fully absorb construction solid waste and industrial solid waste, realize the fixed storage of carbon dioxide, but also realize high-proportion replacement of cement cementitious materials and reduce carbon dioxide emissions.

[0006] The present invention overcomes the shortcomings of the prior art, proposes a composite cementitious material and a preparation method thereof which is mixed with mineralized regenerated micropowder, granulated blast furnace slag, fly ash and kiln dust, obtains granulated blast furnace slag powder through mechanical treatment, obtains mineralized regenerated micropowder through mechanical treatment, mineralization treatment and screening, and evenly mixes the mineralized regenerated micropowder, granulated blast furnace slag, fly ash, kiln dust and cement clinker to obtain the low-carbon composite cementitious material, which can fully utilize the active components in waste concrete powder, blast furnace slag, fly ash and kiln dust, thereby obtaining a low-carbon composite cementitious material equivalent to cement.

[0007] The present invention provides a low-carbon composite cementitious material, which comprises the following components in percentage by mass:

[0008] Cement clinker: 20%~60%;

[0009] Mineralized regenerated powder: 15% to 35%;

[0010] Granulated blast furnace slag: 15% to 45%;

[0011] Fly ash: 2.5% to 10%;

[0012] Kiln dust: 2.5%~5%.

[0013] The beneficial effects of the above technical scheme adopted in the present invention are as follows: the mineralized regenerated micropowder adopted in the present invention can play a certain carbon fixation role in the mineralization treatment process, and the carbon fixation rate can reach about 30%, wherein the main components are calcium carbonate and amorphous silica gel; the granulated blast furnace slag adopted is mainly composed of aluminosilicate, which is a glassy structure material with high activity and can slowly undergo a volcanic ash reaction under alkaline conditions; the fly ash adopted is a volcanic ash material, which can play a micro-aggregate filling effect and promote the development of material strength; the kiln dust adopted is mainly composed of calcium oxide or calcium hydroxide, which can make up for the defect of insufficient alkaline ions caused by the reduction of cement, provide alkaline ions for the system, and promote the volcanic ash reaction of blast furnace slag and fly ash. During the use of the composite cementitious material, the calcium carbonate in the mineralized regenerated micropowder fills the pores of calcium silicate hydrate (CSH) in the cementitious system, provides nucleation sites and exerts a dilution effect, thereby promoting cement hydration, while the amorphous silica gel reacts with calcium hydroxide to generate a cross-linked CSH gel to provide strength; the aluminosilicate in the granulated blast furnace slag can provide nucleation sites and exert a dilution effect in the cementitious system, thereby promoting cement hydration; the kiln dust can provide alkaline ions for the material in the early stage of the material, promoting the volcanic ash reaction of blast furnace slag and fly ash; the fly ash can undergo a volcanic ash reaction under alkaline conditions, generate calcium silicate hydrate (CSH) and play a micro-aggregate filling effect. Under the joint action of multiple substances, the low-carbon composite cementitious material can effectively exert the material performance, and the cement clinker in the material only accounts for 20-60%, that is, the low-carbon composite cementitious material of the present invention can replace cement in a high proportion of 40-80%, effectively reducing the amount of cement clinker, and will not reduce the performance due to the small amount of cement clinker.

[0014] Preferably, the mineralized regenerated micro powder is obtained by mechanically treating, CO 2 Obtained through mineralization, grinding and screening.

[0015] Preferably, the particle size of the mineralized regenerated micro powder is less than 150 μm, the average particle size is 30-40 μm, and the specific surface area is 120-200 m 2 / kg, the content of calcium carbonate in the phase composition is greater than 50%.

[0016] Preferably, the particle size of the granulated blast furnace slag is less than 100 μm; the particle size of the fly ash is less than 100 μm; and the particle size of the kiln dust is less than 200 μm.

[0017] More preferably, the particle size of the mineralized recycled micro powder is less than 75 μm, the particle size of the granulated blast furnace slag is less than 50 μm, the particle size of the fly ash is less than 50 μm, and the particle size of the kiln dust is less than 100 μm;

[0018] Preferably, the cement clinker is a silicate cement clinker with a 28d strength of ≥42.5 MPa, a particle size of less than 40 μm, an average particle size of 5 to 30 μm, and a specific surface area of ​​320 to 430 m 2 / kg.

[0019] More preferably, a low-carbon composite cementitious material comprises the following components in percentage by mass: cement clinker: 20% to 30%; mineralized recycled powder: 25% to 30%; granulated blast furnace slag: 30% to 40%; fly ash: 5% to 10%; kiln dust: 3% to 5%.

[0020] Preferably, the sources of recycled fine powder of waste concrete include but are not limited to various types of construction solid waste such as abandoned buildings, bridges, concrete pavements, etc.

[0021] The present invention also provides a method for preparing the composite gelling material, which comprises the following steps:

[0022] (1) crushing and grinding waste concrete and blast furnace slag, and sieving the ground particles to obtain recycled micro powder with a particle size of less than 150 μm and granulated blast furnace slag with a particle size of less than 100 μm;

[0023] (2) Take the regenerated micropowder in step (1), spray water mist on the regenerated micropowder and mix it evenly, put the pretreated powder into a mineralization reactor and pass CO 2 gas, making the regenerated micro powder and CO 2 Mineralization reaction occurs;

[0024] (3) ball-milling the regenerated micropowder after sufficient reaction in step (2) for a second time, sieving to obtain a powder with a particle size of less than 150 μm, and drying the powder to a constant weight to obtain the mineralized regenerated micropowder;

[0025] (4) The mineralized regenerated fine powder obtained in step (3), the granulated blast furnace slag obtained in step (1), cement clinker, fly ash and kiln dust are mixed uniformly according to the proportion of ingredients to obtain the low-carbon composite cementitious material.

[0026] Preferably, after the powder is pretreated in step (2), the water-to-solid ratio should reach 0.2-0.3:1.0; 2 The volume concentration is between 5 and 100%; the pressure of the mineralization reactor is 0.1 MPa, the temperature is 20 to 30° C., the humidity is 50 to 80% RH, and the reaction time is 8 to 24 hours.

[0027] More preferably, in step (2), the CO in the flue gas 2 The volume concentration is 10-20%, and the reaction time in step (2) is 8-12 hours.

[0028] The beneficial effects of the preferred technical solution of the present invention are as follows: the granulated blast furnace slag, fly ash and kiln dust in step (4) are not subjected to mineralization treatment, wherein the granulated blast furnace slag and fly ash have a Ca, Si, Al, O network structure with pozzolanic activity, so that the nucleation and dilution effects of aluminosilicate are fully exerted in the hydration process of the composite cementitious material, and in the hydration process of the synergistic cement and mineralized regenerated micropowder, the network structure in the blast furnace slag and fly ash undergoes a pozzolanic reaction under the alkaline conditions of cement, and the bonds are broken and reorganized to generate CSH, calcium aluminate hydrate (CAH) or calcium aluminosilicate hydrate. (CSAH) cementitious material; kiln ash contains volcanic ash burnt clay, which can react with cement to form CSH. At the same time, the calcium carbonate in the form of micropowder can accelerate the hydration reaction of the system together with the mineralized regenerated micropowder, and form needle-shaped crystals of calcium carbon aluminate with aluminate. It also plays the role of densely filling micro-aggregate, which can quickly fill in these network structures and play a synergistic role to provide strength for the composite cementitious system. In addition, kiln ash contains a small amount of salt ions (sulfate, chloride), which can play a role in promoting early strength without destroying the system structure.

[0029] The present invention also provides the use of the composite cementitious material in preparing concrete, comprising the following steps:

[0030] Add water to the composite cementitious material according to a water-cement ratio of 0.3-0.4:1, stir for 110-130 seconds, pause for 10-20 seconds, and then stir for 110-130 seconds to obtain a composite cementitious material slurry; pour the composite cementitious material slurry into a mold coated with a lubricant, vibrate and scrape off excess slurry on the surface, put it into an environment of 18-22°C and 90-95% RH for curing for 24 hours, demold, and then cure for 3-28 days to obtain a concrete block.

[0031] Preferably, the low-carbon composite cementitious material can replace the traditional cementitious material, and can be directly applied to concrete, and the concrete strength grade reaches above C50, and can reach up to C60.

[0032] The present invention has the following beneficial effects:

[0033] (1) The low-carbon composite cementitious material of the present invention has high reactivity and can replace cement in a high proportion and be applied to concrete, effectively ensuring the development of system strength;

[0034] (2) The low-carbon composite cementitious material of the present invention can utilize both construction solid waste and industrial solid waste, and has the characteristics of strong applicability, low cost, strong environmental friendliness, and resource recycling;

[0035] (3) The low-carbon composite cementitious material of the present invention can fully utilize the characteristics of each component, so that the system can still achieve a compressive strength of more than C50 at a higher cement replacement amount (70% to 80%);

[0036] (4) The low-carbon composite cementitious material of the present invention can combine CO in the process of preparing mineralized regenerated micropowder. 2 Mineralization effectively realizes the fixation and storage of carbon dioxide. The carbon fixation rate of mineralized recycled micropowder reaches about 30%, and the carbon fixation rate of low-carbon composite cementitious materials is greater than 70 kg CO 2 / ton of cementitious material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a flow chart for the preparation of low-carbon composite cementitious materials;

[0038] Figure 2 It is a flow chart of preparing concrete blocks using low carbon composite cementitious materials. DETAILED DESCRIPTION

[0039] The features and performance of the present invention are further described in detail below in conjunction with embodiments.

[0040] Example 1

[0041] A low-carbon composite cementitious material comprises the following components in percentage by mass: cement clinker: 60%, mineralized recycled micro powder: 15%, granulated blast furnace slag: 20%, fly ash: 2.5%, and kiln dust: 2.5%.

[0042] Example 2

[0043] A low-carbon composite cementitious material comprises the following components in percentage by mass: cement clinker: 40%, mineralized recycled micro powder: 22%, granulated blast furnace slag: 28%, fly ash: 6%, and kiln dust: 4%.

[0044] Example 3

[0045] A low-carbon composite cementitious material comprises the following components in percentage by mass: cement clinker: 20%, mineralized recycled micro powder: 30%, granulated blast furnace slag: 36%, fly ash: 9%, and kiln dust: 5%.

[0046] like Figure 1 As shown, the method for preparing the low-carbon composite cementitious material according to the above formula in each embodiment of the present invention includes the following steps:

[0047] (1) crushing and grinding waste concrete and blast furnace slag by a jaw crusher and a ball mill, and sieving the ball-milled particles by an electric vibrating screen to obtain recycled micro powder with a particle size of less than 150 μm and granulated blast furnace slag with a particle size of less than 100 μm; wherein the waste concrete comes from construction waste of abandoned buildings; the waste concrete has a service life of 12 years and a strength grade of C25;

[0048] (2) Spray water mist onto the regenerated micropowder and mix it evenly, and control the water-solid ratio of the water mist to the initial regenerated micropowder to be 0.25:1.0. Place the pretreated powder into a mineralization reactor, and introduce CO into the mineralization reactor. 2 The volume concentration of flue gas is 20%, the pressure of the mineralization reactor is maintained at 0.1MPa, and the pretreated powder is mineralized for 12 hours at 25°C and 50%RH to obtain mineralized regenerated micro powder;

[0049] (3) ball-milling the mineralized regenerated micropowder for a second time, sieving to obtain a powder with a particle size of less than 150 μm, and drying the powder in a constant temperature drying oven at 105° C. to a constant weight to obtain the mineralized regenerated micropowder;

[0050] (4) According to the material proportions of the above different embodiments, cement clinker, mineralized recycled micro powder, granulated blast furnace slag, fly ash and kiln dust are mixed evenly in a mixer to obtain the low-carbon composite cementitious material.

[0051] like Figure 2 As shown, the application of the low-carbon composite cementitious material prepared in this embodiment in preparing concrete includes the following steps:

[0052] Add water to the low-carbon composite cementitious material at a water-cement ratio of 0.4:1.0, stir for 120 seconds, pause for 15 seconds, and then stir for 120 seconds to obtain a low-carbon composite cementitious material slurry; pour the low-carbon composite cementitious material slurry into a 20×20×20mm 3 In the mold, vibrate and scrape off the excess slurry on the surface, put it into a 20℃, 90% RH environment for curing for 24 hours, demould it, and then cure it for 3 to 28 days to obtain a concrete block.

[0053] Comparative Example 1

[0054] A low-carbon composite cementitious material comprises the following components in percentage by mass: cement clinker: 60%, mineralized recycled micro powder: 15%, granulated blast furnace slag: 20%, fly ash: 5%, kiln dust: 0%. The preparation method of the composite cementitious material in this comparative example is the same as that in the embodiment.

[0055] Comparative Example 2

[0056] A low-carbon composite cementitious material comprises the following components in percentage by mass: cement clinker: 60%, mineralized recycled micro powder: 15%, granulated blast furnace slag: 20%, fly ash: 0%, kiln dust: 5%. The preparation method of the composite cementitious material in this comparative example is the same as that in the embodiment.

[0057] Comparative Example 3

[0058] The comparative example provides an application of cement clinker in preparing pure cement soil blocks, comprising the following steps: mixing water and cement clinker at a water-cement ratio of 0.4:1.0, first slowly stirring for 120 seconds, pausing for 15 seconds and then rapidly stirring for 120 seconds to obtain cement slurry; pouring the cement slurry into a 20×20×20 mm 3 In the cubic mold, vibrate and scrape off the excess slurry on the surface, put it into a constant temperature and humidity autoclave curing box at 20℃ and 95% RH for curing for 24 hours, demould it, and put it into the constant temperature and humidity autoclave curing box for the second curing for 3 to 28 days to obtain a pure cement concrete block.

[0059] Comparative Example 4

[0060] A composite cementitious material doped with mineralized recycled micropowder and a preparation method thereof, comprising the following steps:

[0061] (1) crushing and grinding the waste concrete by a jaw crusher and a ball mill, and sieving the ball-milled particles by an electric vibrating screen to obtain recycled micro powder with a particle size of less than 150 μm; wherein the waste concrete comes from construction waste of abandoned buildings; the waste concrete has a service life of 12 years and a strength grade of C25;

[0062] (2) Spray water mist onto the regenerated micropowder and mix it evenly, and control the water-solid ratio of the water mist to the initial regenerated micropowder to be 0.25:1.0. Place the pretreated powder into a mineralization reactor, and introduce CO into the mineralization reactor. 2 The volume concentration of flue gas is 20%, the pressure of the mineralization reactor is maintained at 0.1MPa, and the pretreated powder is mineralized for 12 hours at 25°C and 50%RH to obtain mineralized regenerated micro powder;

[0063] (3) ball-milling the mineralized regenerated micropowder for a second time, sieving to obtain a powder with a particle size of less than 150 μm, and drying the powder in a constant temperature drying oven at 105° C. to a constant weight to obtain the mineralized regenerated micropowder;

[0064] (4) 60% of cement clinker and 40% of mineralized recycled micro powder are mixed evenly in a mixer to obtain a composite cementitious material.

[0065] The application of the composite cementitious material prepared in this embodiment in preparing concrete is carried out in the same steps as in the embodiment.

[0066] Comparative Example 5

[0067] The preparation method of the composite cementitious material solely doped with mineralized regenerated micropowder in this comparative example is the same as that in comparative example 2; in the preparation of the composite cementitious material, 40% of cement clinker and 60% of mineralized regenerated micropowder are evenly mixed, and the remaining steps are the same as those in comparative example 4.

[0068] Comparative Example 6

[0069] A composite cementitious material containing only granulated blast furnace slag and a preparation method thereof, comprising the following steps:

[0070] (1) crushing and grinding blast furnace slag with a jaw crusher and a ball mill, and screening the ball-milled particles with an electric vibrating screen to obtain granulated blast furnace slag with a particle size of less than 100 μm; the blast furnace slag comes from the steel industry;

[0071] (2) 60% of cement clinker and 40% of granulated blast furnace slag are mixed evenly in a mixer to obtain a composite cementitious material.

[0072] The application of the composite cementitious material prepared in this comparative example in preparing concrete is carried out in the same steps as those in the embodiment.

[0073] Comparative Example 7

[0074] The preparation method of the composite cementitious material with only granulated blast furnace slag in this comparative example is the same as that in comparative example 6; in the preparation of the composite cementitious material, 40% cement clinker and 60% granulated blast furnace slag are mixed evenly, and the remaining steps are the same as those in comparative example 6.

[0075] Comparative Example 8

[0076] A composite cementitious material mixed with mineralized recycled micro powder and granulated blast furnace slag and a preparation method thereof, comprising the following steps:

[0077] (1) crushing and grinding waste concrete and blast furnace slag by a jaw crusher and a ball mill, and sieving the ball-milled particles by an electric vibrating screen to obtain recycled micro powder with a particle size of less than 150 μm and granulated blast furnace slag with a particle size of less than 100 μm; wherein the waste concrete comes from construction waste of abandoned buildings; the waste concrete has a service life of 12 years and a strength grade of C25;

[0078] (2) Spray water mist onto the regenerated micropowder and mix it evenly, and control the water-solid ratio of the water mist to the initial regenerated micropowder to be 0.25:1.0. Place the pretreated powder into a mineralization reactor, and introduce CO into the mineralization reactor. 2The volume concentration of flue gas is 20%, the pressure of the mineralization reactor is maintained at 0.1MPa, and the pretreated powder is mineralized for 12 hours at 25°C and 50%RH to obtain mineralized regenerated micro powder;

[0079] (3) ball-milling the mineralized regenerated micropowder for a second time, sieving to obtain a powder with a particle size of less than 150 μm, and drying the powder in a constant temperature drying oven at 105° C. to a constant weight to obtain the mineralized regenerated micropowder;

[0080] (4) According to the material proportions of the above different embodiments, 60% of cement clinker, 20% of mineralized recycled micropowder and 20% of granulated blast furnace slag are mixed evenly in a mixer to obtain the composite cementitious material.

[0081] The application of the composite cementitious material prepared in this comparative example in preparing concrete is carried out in the same steps as those in the embodiment.

[0082] Comparative Example 9

[0083] The composite cementitious material mixed with mineralized recycled micropowder and granulated blast furnace slag and the preparation method in this comparative example are the same as those in comparative example 8; in the preparation of the composite cementitious material, 40% cement clinker, 30% mineralized recycled micropowder and 30% granulated blast furnace slag are mixed evenly, and the remaining steps are the same as those in comparative example 8.

[0084] Experimental example

[0085] 1. The chemical composition of each solid waste such as mineralized recycled micro powder, granulated blast furnace slag, fly ash and kiln dust involved in the examples and comparative examples was measured, and the results are shown in Table 1. At the same time, the content of free calcium oxide and calcium carbonate in the kiln dust reached more than 10%.

[0086] Table 1 Chemical composition of each component

[0087]

[0088]

[0089] 2. The apparent carbon fixation amount of the mineralized regenerated micropowder prepared in the embodiment and the comparative example was tested. Calcium carbonate decomposes at 500°C to 850°C to cause mass loss. The present invention adopts a pyrolysis method to test the weight loss of the mineralized regenerated micropowder in the range of 500°C to 850°C. 2 The mass loss of carbonate decomposition was normalized according to the initial powder mass, and the apparent carbon fixation of the mineralized regenerated micropowder was calculated to be 28.3%.

[0090] 3. The concrete blocks prepared in Examples 1 to 3 and Comparative Examples 1 to 9 were subjected to compressive strength tests at 3d, 7d and 28d after the second curing. The compressive strength test was carried out in accordance with the cement paste strength test method GB / T17671-2021 (ISO method). The results are shown in Table 2.

[0091] Table 2 Compressive strength test results of concrete blocks after second curing at different times

[0092]

[0093] The concrete blocks prepared in Examples 1 to 3 and Comparative Examples 1 to 9 were tested for compressive strength at 3d, 7d and 28d of the second curing. From the results in Table 1, it can be seen that the concrete blocks prepared in Examples 1 to 3 have high early and late strengths, specifically, the strength at 3d is ≥35MPa, the strength at 7d is ≥44MPa, and the strength at 28d is ≥57MPa. Among them, the concrete blocks prepared in Example 3 have a strength of 36.25MPa at 3d of the second curing, a strength of 45.55MPa at 7d and a strength of 57.26MPa at 28d, and their strength performance is basically equivalent to that of pure cement blocks, indicating that the low-carbon composite cementitious material mixed with mineralized recycled micropowder, granulated blast furnace slag, fly ash and kiln dust has excellent performance and can effectively replace 80% of silicate cement clinker.

[0094] Compared with the low-carbon composite cementitious material prepared in Example 1, the composite cementitious material prepared in Comparative Example 1 is used to prepare concrete blocks (without adding fly ash), and its compressive strength after the second curing for 3d, 7d and 28d is 32.29MPa, 40.16MPa and 54.85MPa respectively. The composite cementitious material prepared in Comparative Example 2 is used to prepare concrete blocks (without adding fly ash), and its compressive strength after the second curing for 3d, 7d and 28d is 35.12MPa, 41.98MPa and 49.34MPa respectively. It can be seen that the composite cementitious material prepared by adding fly ash alone has a poor early strength of 3d, which is only 89.4% of that in Example 1, and a better late strength of 28d, which can reach 93.4% of that in Example 1; the composite cementitious material prepared by adding fly ash alone has a better early strength of 3d, which can reach 97.2% of that in Example 1, and a poor late strength of 28d, which is only 84.1% of that in Example 1. This is because the introduction of fly ash into the system of cement, mineralized recycled micropowder and blast furnace slag can not only ensure the alkalinity of the system, promote the pozzolanic reaction of granulated blast furnace slag and fly ash and the formation of CSH, but also promote the development of early strength of the system by introducing salt ions; the introduction of fly ash can cause a micro-aggregate effect, promote the hydration reaction of cement and the pozzolanic reaction of granulated blast furnace slag. Therefore, compared with the system of single fly ash or fly ash, the introduction of fly ash and fly ash into the system of cement, mineralized recycled micropowder and blast furnace slag can make the low-carbon composite cementitious material have excellent early strength and late strength at the same time.

[0095] Compared with the pure cement blocks prepared in Comparative Example 3, the composite cementitious materials prepared in Comparative Examples 4 to 5 with single addition of mineralized recycled powder are used to prepare concrete blocks, and their compressive strength decreases after the second curing for 3d, 7d and 28d, and the strength gradually decreases with the increase of the amount of mineralized recycled powder added. Among them, in Comparative Example 5, the concrete blocks prepared with 60% mineralized recycled powder and 40% cement clinker have a strength of 18.45MPa at 3d of the second curing, 26.54MPa at 7d and 44.73MPa at 28d. This shows that the addition of mineralized recycled powder will affect the hydration performance of the cement system itself. When the amount of mineralized recycled powder added is too much, the cement hydration product CSH is significantly reduced, making the structure of the system unstable, so the compressive strength of the prepared concrete blocks gradually decreases.

[0096] Compared with the pure cement blocks prepared in Comparative Example 3, the composite cementitious materials prepared in Comparative Examples 6-7 with only granulated blast furnace slag were used to prepare concrete blocks. With the increase of the granulated blast furnace slag content, the compressive strength after the second curing for 3d and 7d was significantly reduced, while the compressive strength after 28d curing did not change much. Among them, in Comparative Example 5, the concrete blocks prepared with 60% granulated blast furnace slag and 40% cement clinker had a strength of 21.98MPa at 3d, 33.23MPa at 7d, and 50.25MPa at 28d after the second curing. This shows that the addition of granulated blast furnace slag will significantly affect the early strength of the cement system, while the effect on the later strength is relatively small, only decreasing by about 17.6%.

[0097] Comparative Examples 1 to 3 and Comparative Examples 4 to 9, the concrete blocks prepared by the low-carbon composite cementitious material of the present invention, which is mixed with mineralized regenerated micropowder, granulated blast furnace slag, fly ash and kiln dust, have a compressive strength significantly higher than that of the system of single-mixed mineralized regenerated micropowder or granulated blast furnace slag. The introduction of mineralized regenerated micropowder can ensure the early strength of the composite cementitious material and fix part of the carbon dioxide at the same time; the introduction of granulated blast furnace slag and fly ash can ensure the later strength of the composite cementitious material, and the introduction of fly ash can also promote the micro-aggregate phenomenon in the system and promote the cement hydration reaction; kiln dust can introduce a small amount of salt ions (sulfate, chloride), which can play an early strength promoting role without destroying the system structure, and at the same time can ensure the alkalinity of the system, promote the hydration reaction of the system, and ensure the early strength of the composite cementitious material; under the joint action of multiple effects, cement can be replaced by a high ratio of 60% to form a composite cementitious material with performance very close to that of pure cement. The concrete blocks prepared by using 40% cement clinker, 25% mineralized recycled powder, 27% granulated blast furnace slag, 5% fly ash and 3% kiln dust in Example 2 have a strength of more than 95% of the strength of pure cement blocks at the second curing of 3d, 7d and 28d, and a strength of more than 97% at 28d.

[0098] In summary, the low-carbon composite cementitious material mixed with mineralized recycled micropowder, granulated blast furnace slag, fly ash and kiln dust can achieve 70 kg CO 2 / ton cementitious material. It can replace up to 60% of Portland cement without affecting the early and late compressive strength of concrete blocks; it can replace up to 80% of Portland cement without considering the early strength of concrete blocks. It is an excellent cement substitute material.

[0099] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.

Claims

1. A low-carbon composite cementitious material, characterized in that: The following components are included in mass percentage: Cement clinker: 20%~60%; Mineralized regenerated powder: 15% to 35%; Granulated blast furnace slag: 15% to 45%; Fly ash: 2.5% to 10%; Kiln dust: 2.5%~5%.

2. A low-carbon composite cementitious material according to claim 1, characterized in that: The invention comprises the following components in percentage by mass: cement clinker: 20%-30%; mineralized recycled micro powder: 25%-30%; granulated blast furnace slag: 30%-40%; fly ash: 5%-10%; kiln dust: 3%-5%.

3. A low-carbon composite cementitious material according to claim 1, characterized in that: The mineralized regenerated micro powder is obtained by subjecting the regenerated micro powder of waste concrete to mechanical treatment, CO2 mineralization treatment, grinding and screening.

4. The low-carbon composite cementitious material according to claim 1, characterized in that: The particle size of the mineralized regenerated micro powder is less than 150 μm, and the content of calcium carbonate in the phase composition is greater than 50%; the particle size of the granulated blast furnace slag is less than 100 μm; the particle size of the fly ash is less than 100 μm; and the particle size of the kiln dust is less than 100 μm.

5. The low-carbon composite cementitious material according to claim 1, characterized in that: The cement clinker is silicate cement clinker with a 28d strength of ≥42.5MPa and a particle size of less than 40μm.

6. The low-carbon composite cementitious material according to claim 3, characterized in that: The recycled fine powder of the waste concrete comes from waste buildings, bridges and concrete pavements.

7. A method for preparing the low-carbon composite cementitious material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) crushing and grinding waste concrete and blast furnace slag, and sieving the ground particles to obtain recycled micro powder with a particle size of less than 150 μm and granulated blast furnace slag with a particle size of less than 100 μm; (2) taking the regenerated micropowder in step (1), spraying water mist on the regenerated micropowder and mixing it evenly, placing the pretreated powder into a mineralization reactor and introducing CO2 gas to allow the regenerated micropowder to undergo a mineralization reaction with CO2; (3) ball-milling the regenerated micropowder after sufficient reaction in step (2) for a second time, sieving to obtain a powder with a particle size of less than 150 μm, and drying the powder to a constant weight to obtain the mineralized regenerated micropowder; (4) The mineralized regenerated fine powder obtained in step (3), the granulated blast furnace slag obtained in step (1), cement clinker, fly ash and kiln dust are mixed uniformly according to the proportion of ingredients to obtain the low-carbon composite cementitious material.

8. A low-carbon composite cementitious material and preparation method according to claim 7, characterized in that: After the powder is pretreated in step (2), the water-solid ratio should reach 0.2-0.3:1.0; the volume concentration of CO2 in the flue gas in step (2) is between 5% and 100%, the pressure of the mineralization reactor is 0.1MPa, the temperature is 20-30°C, the humidity is 50-80%RH, and the reaction time is 8-24h.

9. Use of the low-carbon composite cementitious material according to any one of claims 1 to 6 in replacing cement cementitious material in the preparation of concrete products.

10. The use according to claim 9, characterized in that: Add water to the composite cementitious material according to a water-cement ratio of 0.3-0.4:1, stir for 110-130 seconds, pause for 10-20 seconds, and then stir for 110-130 seconds to obtain a composite cementitious material slurry; pour the composite cementitious material slurry into a mold coated with a lubricant, vibrate and scrape off excess slurry on the surface, put it into an environment of 18-22° C. and 90-95% RH for curing for 24 hours, demold, and then cure for 3-28 days to obtain a concrete block.